Can Healthcare Assistant Training (CHAT) improve the relational care of older people? Study protocol for a pilot cluster randomised controlled trial. Issue 1 (December 2015) - Arthur, Antony; Maben, Jill; Wharrad, Heather; Aldus, Clare; Sarre, Sophie; Schneider, Justine; Nicholson, Caroline; Barton, Garry; Cox, Karen; Clark, Allan
Abstract Background People aged 75 years and over account for 1 in 4 of all hospital admissions. There has been increasing recognition of problems in the care of older people, particularly in hospitals. Evidence suggests that older people judge the care they receive in terms of kindness, empathy, compassion, respectful communication and being seen as a person not just a patient. These are aspects of care to which we refer when we use the term 'relational care'. Healthcare assistants deliver an increasing proportion of direct care to older people, yet their training needs are often overlooked. Methods/Design This study will determine the acceptability and feasibility of a cluster randomised controlled trial of 'Older People's Shoes' a 2-day training intervention for healthcare assistants caring for older people in hospital. Within this pilot, 2-arm, parallel, cluster randomised controlled trial, healthcare assistants within acute hospital wards are randomised to either the 2-day training intervention or training as usual. Registered nurses deliver 'Older People's Shoes' over 2 days, approximately 1 week apart. It contains three components: experiential learning about ageing, exploration of older people's stories, and customer care. Outcomes will be measured at the level of patient (experience of emotional care and quality of life during their hospital stay), healthcare assistant (empathy and attitudes towards older people), and ward (quality of staff/patient interaction). Semi-structured interviews of a purposive sample of healthcare assistants receiving the intervention, and all trainers delivering the intervention, will be undertaken to gain insights into the experiences of both the intervention and the trial, and its perceived impact on practice. Discussion Few training interventions for care staff have been rigorously tested using randomised designs. This study will establish the viability of a definitive cluster randomised controlled trial of a new training intervention to improve the relational care proided by healthcare assistants working with older people in hospital. Trial registration The study was registered as an International Standard Randomised Controlled Trial (ISRCTN10385799 ) on 29 December 2014.